System identification of parameterized state-space model of a small scale UAV helicopter - Ismaila B., Tijani; Akmeliawati, Rini; Legowo, Ari (2012)
The success of model-based ight control law design for autonomous helicopter is largely dependent on the availability of reliable model of the system. Considering the complexity of the helicopter dynamics, and inherent diculty involves with physical measurement of the system parameters, the grey modeling approach which involves the development of parameterized model from rst principles and estimation of these parameters using system identication (sysID) technique has been proposed in the literatures. Prediction Error Modeling (PEM) algorithm has been identied as an eective system identication technique. However, application of this method to complex system like helicopter is not a trivial exercise due to inherent coupling in the system states and the challenges associated with parameter initialization in PEM algorithm. In this work, an eective procedure in application of PEM algorithm available in MATLAB toolbox is presented for small scale helicopter using real-time ight data. The approach was able to yield satisfactory model suitable for model-based ight control design.